Inovasi Media Pembelajaran Tematik Kontekstual Berbasis Multikultural: Kolaborasi Penguatan Kemitraan PAUD dan Orang Tua - Daryati, Melia Eka; Sari, Julia Purnama; Suryadi, Didik (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Strengthening partnerships between early childhood education institutions and parents is an important strategy in supporting optimal child growth and development. However, facts on the ground show that parental involvement in the learning process is still limited, so there is a need for innovative learning media that connects the roles of teachers and parents. The community service activity aims to improve the understanding and skills of early childhood teachers and parents in using contextual thematic learning media based on multicultural wisdom. The community service method involved counseling, training, and collaborative assistance. There were 25 participants consisting of PAUD teachers and parents of students. The evaluation results showed a significant increase in understanding from a pre-test score of 55.8 to a post-test score of 88.4, with an average increase of 32.6 points. These findings show that the innovation of learning media based on multicultural values not only strengthens the role of parents in children's education but also creates a more contextual and inclusive learning environment. This community service activity contributes to the establishment of a sustainable partnership between early childhood education and parents in supporting the quality of early childhood education.